Fire analysis of structures in terms of physical phenomena observed during uniaxial tensile tests of steel - Skowroński, Wojciech (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
Calculation Methods for building structures in fire should allow a thorough analysis and take into account the specific characteristics of heated materials such as steel’s non-linear creep. Theoretical consideration about metal structures in a fire might be verified and supplemented by the results of the material and fire tests. The main objectives of the research on structure material at elevated temperature is to assign the strength and thermal characteristics. The results of the standard fire tests determine the reaction of the element separated from a structure on the heating according to a standard curve ‘temperature-time”. The standard reduction of the real fire scenarios results, among the others, from the limited opportunities of the laboratory testing.